Pengaruh Komitmen Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan - Riris Anggun Cahyani (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
ABSTRAK This study aims to analyze the effect of organizational commitment and job satisfaction on the performance of PDAM Salatiga City employees. The object under study was PDAM Salatiga City employees. Data collection techniques using purposive sampling method with a focus on employees who have worked at least one year at the company. The study used primary data in the form of a questionnaire of 60 respondents with a 92.3% return rate. Data were analyzed using multiple linear regression analysis to measure the magnitude of the influence of organizational commitment and job satisfaction on employee performance. The results showed that organizational commitment had a positive effect on employee performance, job satisfaction had a positive effect on employee performance and together organizational commitment and job satisfaction had a positive effect on employee performance. Keywords: Organizational Commitment, Job Satisfaction, and Employee Performance